Halophilic and halotolerant fungi across diverse climates: a comparative study of Polish and Italian soil ecosystems - Śliżewska, Weronika; Struszczyk-Świta, Katarzyna; Otlewska, Anna; Pinzari, Flavia; Canfora, Loredana; Dybka-Stȩpień, Katarzyna; Napoli, Rosario; Migliore, Melania; Manfredini, Andrea; Marchut-Mikołajczyk, Olga (Frontiers in Microbiology, 2025)
This study investigated agricultural saline soils collected from distinct pedoclimatic profiles from Poland and Italy. Twelve fungal strains from Italy and 9 from Poland were identified and tested for halotolerance, extracellular enzyme production, biosurfactant potential, and mycotoxin production. The tested strains were affiliated to 8 genera, with Aspergillus and Penicillium being the most predominant. All tested strains were confirmed to be good producers of at least one of the analyzed hydrolytic enzymes, with cellulase being the most frequently produced. Notably, Ramularia mali FF1 was the best producer of the tested extracellular enzymes and showed the highest enzymatic activity for amylase, cellulase, chitosanase, pectinase and xylanase among all strains. A hemolytic assay was implemented to evaluate the potential for biosurfactant production in media supplemented with various sodium chloride concentrations. Among 21 tested strains, 14 demonstrated hemolytic activity at 5% NaCl. Based on the results, Acremonium sclerotigenum FF3 was selected to perform biosurfactant analysis. Mycotoxin screening revealed that Penicillium canescens S10 was the only producer of any examined mycotoxin, with 5.759 μg/mL concentration of ochratoxin A. This research underscores the varied enzymatic and biosurfactant capabilities of halophilic fungi adapted to saline soils and highlight the biotechnological potential of these organisms and environments.